High circulating oestrone and low testosterone correlate with adverse clinical outcomes in men with advanced liver disease. (6th April 2016) - Sinclair, Marie; Gow, Paul J.; Angus, Peter W.; Hoermann, Rudolf; Handelsman, David J.; Wittert, Gary; Martin, Sean; Grossmann, Mathis
Abstract: Background & Aims: Circulating testosterone is usually reduced in men with cirrhosis, but there has not been a comprehensive analysis of androgen status or circulating oestrogens. Little is known about associations between circulating sex steroids with aspects of health in this population. Methods: We report data from men with cirrhosis and low serum testosterone (<12 nmol/L or calculated free testosterone <230 pmol/L). Comprehensive circulating sex steroid profiles were measured by liquid chromatography‐mass spectrometry and compared with age‐matched controls. Relationships between sex hormone levels, severity of liver disease, biochemistry and clinical outcomes were assessed. Results: Serum oestrone and oestradiol were significantly elevated in men with cirrhosis compared with controls (median, 869.1 pmol/L vs. 133.8 pmol/L and 166.7 pmol/L vs. 84.6 pmol/L respectively). Serum oestrone correlated with MELD score (correlation +0.306, P < 0.001) and inversely correlated with serum sodium (correlation −0.208, P = 0.004) and haemoglobin (correlation −0.177, P = 0.012). No such correlations were observed for oestradiol. Serum testosterone levels inversely correlated with MELD score (correlation −0.294, P < 0.001) and positively with handgrip strength (correlation +0.242, P < 0.001), physical activity (correlation +0.276, P = 0.012), haemoglobin (correlation +0.282, P < 0.001) and serum sodium (+0.344, P < 0.001). Dihydrotestosterone inversely correlated with MELD score (correlation −0.225, P = 0.002) and shared similar significant relationships to testosterone. Conclusion: Low serum androgens and elevated serum oestrone (but not oestradiol) are associated with higher MELD and individual adverse health outcomes in cirrhotic cohort of men selected for low testosterone. Serum oestrone may be a novel marker of ill health in this population. Whether low androgens are markers or mediators of ill health requires further investigation.